Climate and soil shape Daqu wheat quality and seed microbiome via rhizosphere taxa and microbial assembly - Kangjie Yu; Shuanghui Wang; Hanrui Shi; Rui Luo; Zijian Chen; Yi Xia; Qingdong Zeng; Yi Ma; Dejun Han (Food Research International, 2026)

Direct upcycling spent LiCoO2 into self-supporting cathodes via cobalt-seed induced slurry electrolysis - Yunhui Han; Xiangfei Zeng; Dejun He; Jiqin Wang; Kun Li; Qian Liang; Ling Hu; Anlong Han; Hao Li; Mengjun Chen (Chemical Engineering Journal, 2026)

SIRT7-mediated H3K79 desuccinylation modulates functional activities of goat ovarian granulosa cells - Yawen Li; Lei Wang; Shuaifei Song; Qiuyan Li; Ying Gong; Zihan Wang; Shiyi Yao; Zihan Ma; Yingping Xia; Cong Zhou; Xinyang Yao; Jia Luo; et al. (Theriogenology, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Hydration mechanism, mechanical properties and environmental performance of electrolytic manganese residue based total solid waste supersulfate cement - Dejun He; Junying Li; Guiji Tu; Mengjun Chen; Yunhui Han (Process Safety and Environmental Protection, 2026)

Modeling the coupled dynamics of a remotely operated vehicle during underwater launch - Ruinan Guo; Yingfei Zan; Ning He; Shan Wang; Duanfeng Han; Lihui Li; Dejun Li (Ocean Engineering, 2026)

Precise mapping of high-temperature adult-plant stripe rust resistance gene Yr52 in wheat - Mingjie Xiang; Yibo Zhang; Shuaiwei Cao; Jiangna Han; Haohao Yan; Chenfang Wu; Jiale Li; Xunying Yuan; Xiangrui Cheng; Shuqing Yang; Zhuang Li; Xiaoting Wang; et al. (Theoretical and Applied Genetics, 2026)

Performance enhancement mechanisms and applications of micropressure internal circulation reactors driven by flow pattern optimization - Xuejian Sun; Qing Qiu; Fan Wang; Han Li; Dejun Bian; Hongliang Huo (Process Safety and Environmental Protection, 2026)

Electrochemical oscillation on lead recovery from spent lead paste by suspension electrolysis - Xingyu Luo; Jiqin Wang; Dejun He; Yunhui Han; Xiangfei Zeng; Ling Hu; Qian Liang; Hao Li; Anlong Han; Jianchen Shu; Mengjun Chen (Journal of Environmental Chemical Engineering, 2026)

Stochastic and deterministic processes shape microbiota and flavors of strong-flavor Daqu made from different wheat varieties during fermentation - Kangjie Yu; Rong Yang; Huiling Huang; Shuanghui Wang; Chaojiu He; Liya Huang; Yi Ma; Dejun Han (Food Research International, 2026)

An integrated atmospheric-topographic correction framework for land surface reflectance estimation using a spatial-spectral Attention U-Net model - Yichuan Ma; Shunlin Liang; Han Ma; Tao He; Xiran Shi; Wenyuan Li; Dejun Cai; Xiongxin Xiao; Shikang Guan; Weiwei Liu; Jianglei Xu; Yongzhe Chen; et al. (Remote Sensing of Environment, 2026)

Genome-wide identification of TGA transcription factors in wheat and the TaTGA13 negatively modulates stripe rust resistance - Jiajie Liu; Rui Li; Mingjie Xiang; Xunyin Yuan; Yifan Tian; Xuanqi Zhang; Jingyao Wang; Jianhui Wu; Qingdong Zeng; Dejun Han (Plant Science, 2026)

Supercritical CO2-assisted pressure homogenization for exfoliating natural graphite toward high-performance graphene cathodes in aluminum-ion batteries - Yue Wu; Jianmin Feng; Li Wang; Jiacheng Qiu; Xuan Song; Xuwang Fu; Ziqi Luo; Jiahan Ma; Xiaoyu Yu; Lei Dong; Yan Han; Conglai Long; et al. (Chemical Engineering Journal, 2025)

Mapping QTLs for adult-plant resistance to yellow rust in a hard winter wheat population Heyne × Lakin - Chunlian Li; Xiao-Ting Xu; Yibo Zhang; Shengjie Liu; Jianhui Wu; Dejun Han; Robert Bowden; John Fellers; Guihua Bai (Theoretical and Applied Genetics, 2025)

Genotyping by target sequencing (GBTS)-based genetic mapping uncovers synergistic interactions for stripe rust resistance in wheat cultivar Flanders - Lei Liu; Jinyu Han; Dandan Zhang; Yuqing Li; Chuanliang Zhang; Shengjie Liu; Ziyi Yan; Weijun Zheng; Chunlian Li; Qingdong Zeng; Zhensheng Kang; Dejun Han; et al. (Theoretical and Applied Genetics, 2025)

N/O co-doped hollow sphere-like hard carbon with hierarchical pores for fast and high-capacity Na+/Li+ storage - Chenchen Bai; Bingjun Li; Chang Shu; Wenjie Chen; Yan Han; Dejun Li (Chemical Engineering Journal, 2025)

Contrasting roles of abundant and rare root-associated fungi in wheat: Community assembly, heritability and agronomic impacts - Xia Kang; Yuyin Zheng; Zhihan Feng; Minjie Yao; Xiangzhen Li; Dejun Han; Qingdong Zeng; Hao Tan; Yumin Yang; Jiabao Li (Applied Soil Ecology, 2025)

Decadal trends of black carbon and heavy metal accumulation in a lake sediment core from central China: A historical perspective - Changlin Zhan; Dejun Wan; Yongming Han; Jiaquan Zhang; Shan Liu; Hongxia Liu; Tianpeng Hu; Wensheng Xiao; Junji Cao; Dong Li (CATENA, 2024)

Evaluation of hydrodynamic coefficients and sensitivity analysis of a work-class remotely operated vehicle using planar motion mechanism tests - Ruinan Guo; Yingfei Zan; Xiaofang Luo; Xiandong Ma; Tiaojian Xu; Duanfeng Han; Dejun Li; Xu Bai (Ocean Engineering, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Sources and factors influencing lacustrine carbon burial over the last century: case study of Yinjia Lake, central China - Changlin Zhan; Dejun Wan; Yongming Han; Shan Liu; Jiaquan Zhang; Hongxia Liu; Tianpeng Hu; Wensheng Xiao; Junji Cao (Journal of Paleolimnology, 2024)

High-density mapping of durable and broad-spectrum stripe rust resistance gene Yr30 in wheat - Xiaoting Wang; Mingjie Xiang; Huaizhou Li; Xiaoxiao Li; Keqing Mu; Shuo Huang; Yibo Zhang; Xiangrui Cheng; Shuqing Yang; Xunying Yuan; Ravi P. Singh; Sridhar Bhavani; et al. (Theoretical and Applied Genetics, 2024)

Genome-wide association study revealed the reason for the decrease in grain iron concentration during wheat breeding process in China - Jianhui Ma; Yize Wang; Shuya Li; Qianqian Liu; Meng Yuan; Chunci Li; Daijing Zhang; Qingdong Zeng; Jianhui Wu; Chengxiang Song; Wei Li; Dejun Han; et al. (Field Crops Research, 2024)

Luteolin inhibits the JAK/STAT pathway to alleviate auditory cell apoptosis of acquired sensorineural hearing loss based on network pharmacology, molecular docking, molecular dynamics simulation, and experiments in vitro - Fang Guo; Yingyuan Guo; Dejun Zhang; Zeming Fu; Shuang Han; Yining Wan; Guofang Guan (Toxicology and Applied Pharmacology, 2024)

Sediment records of black carbon variations over the last two centuries in North China - Dejun Wan; Yongming Han; Lei Song; Dongliang Ning; Qingfeng Jiang (Science of The Total Environment, 2023)

Highly effective corneal permeability of reactive oxygen species-responsive nano-formulation encapsulated cyclosporine a for dry eye management - Dejun Yang; Yi Han; Yili Wang; Yingying Pan; Lan Zheng; Zuguo Liu; Cheng Li; Yunlong Wu; Huaqiong Li (Chemical Engineering Journal, 2023)

Slow stripe rusting in Chinese wheat Jimai 44 conferred by Yr29 in combination with a major QTL on chromosome arm 6AL - Shengjie Liu; Dan Liu; Chuanliang Zhang; Wenjing Zhang; Xiaoting Wang; Zhiwen Mi; Xin Gao; Yong Ren; Caixia Lan; Xiukun Liu; Zhendong Zhao; Jianjun Liu; et al. (Theoretical and Applied Genetics, 2023)

Genome-wide association study reveals the genetic variation and candidate gene for grain calcium content in bread wheat - Jianhui Ma; Jingjie Ren; Xuqing Yuan; Meng Yuan; Daijing Zhang; Chunxi Li; Qingdong Zeng; Jianhui Wu; Dejun Han; Lina Jiang (Plant Cell Reports, 2023)

Molecular characterization and validation of adult-plant stripe rust resistance gene Yr86 in Chinese wheat cultivar Zhongmai 895 - Zhanwang Zhu; Qiang Cao; Dejun Han; Jianhui Wu; Ling Wu; Jingyang Tong; Xiaowan Xu; Jun Yan; Yong Zhang; Kaijie Xu; Fengju Wang; Yachao Dong; et al. (Theoretical and Applied Genetics, 2023)

Zinc efficiently extracted from zinc calcine by reduced wet grinding: ZnFe2O4 to ZnO and Fe3O4 - Shaoqin Chen; Xiangfei Zeng; Qian Liang; Ling Hu; Shuyuan Chen; Dejun He; Yunhui Han; Zhisheng Zhao; Rong Huang; Yin Huang; Songshan Zhou; Jiqin Wang; et al. (Journal of Cleaner Production, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

Epistatic interaction effect between chromosome 1BL (Yr29) and a novel locus on 2AL facilitating resistance to stripe rust in Chinese wheat Changwu 357-9 - Shuo Huang; Yibo Zhang; Hui Ren; Xiang Li; Xin Zhang; Zeyuan Zhang; Chuanliang Zhang; Shengjie Liu; Xiaoting Wang; Qingdong Zeng; Qilin Wang; Ravi P. Singh; et al. (Theoretical and Applied Genetics, 2022)

Enhanced stripe rust resistance obtained by combining Yr30 with a widely dispersed, consistent QTL on chromosome arm 4BL - Shengjie Liu; Xiaoting Wang; Yayun Zhang; Yangang Jin; Zhonghua Xia; Mingjie Xiang; Shuo Huang; Linyi Qiao; Weijun Zheng; Qingdong Zeng; Qilin Wang; Rui Yu; et al. (Theoretical and Applied Genetics, 2022)

Spatial and Seasonal Distribution of 2-Methylisoborneol in a Large Eutrophic Shallow Lake, China - Anjie Wu; Yadong Wang; Kurt Friese; Lu Zhang; Chao Han; Dejun Kang; Qiushi Shen (Water, Air, & Soil Pollution, 2021)

Refined mapping of stripe rust resistance gene YrP10090 within a desirable haplotype for wheat improvement on chromosome 6A - Shengjie Liu; Shuo Huang; Qingdong Zeng; Xiaoting Wang; Rui Yu; Qilin Wang; Ravi P. Singh; Sridhar Bhavani; Zhensheng Kang; Jianhui Wu; Dejun Han (Theoretical and Applied Genetics, 2021)

Wheat-root associated prokaryotic community: interplay between plant selection and location - Yuyin Zheng; Zhihan Feng; Jialong Wang; Xiaoman Huang; Li Lei; Xue Zhang; Huili Cao; Dandan Fan; Minjie Yao; Dejun Han; Xiangzhen Li (Plant and Soil, 2021)

The Adsorptive Ability of 3D Flower-Like Titanium Phosphate for U(VI) in Aqueous Solution - Youqun Wang; Dejun Zeng; Ying Dai; Chenglei Fang; Xuewen Han; Zhibin Zhang; Xiaohong Cao; Yunhai Liu (Water, Air, & Soil Pollution, 2020)

Stripe rust resistance genes in a set of Ethiopian bread wheat cultivars and breeding lines - Zeray Siyoum Gebreslasie; Shuo Huang; Gangming Zhan; Ayele Badebo; Qingdong Zeng; Jianhui Wu; Qilin Wang; Shengjie Liu; Lili Huang; Xiaojing Wang; Zhensheng Kang; Dejun Han (Euphytica, 2020)
Stripe rust caused by Puccinia striiformis f. sp . tritici ( Pst ) is one the most important diseases of wheat in Ethiopia and worldwide. To identify resistance genes, 90 bread wheat lines and 10 cultivars were tested at the seedling stage against one Pst race from Ethiopia and six races from China as well as evaluated for the stripe rust response in an inoculated field nursery at Yangling, Shaanxi province and in a naturally infected field in Jiangyou, Sichuan, China. Resistance genes were postulated using molecular assays for Yr9 , Yr17, Yr18, Yr26, Yr29, Yr36, Yr44 and Yr62. Of the 100 entries tested, 16 had all stage resistance to all races. Molecular markers were positive for Yr9 in five genotypes, Yr17 in 21 genotypes, Yr18 in 27 genotypes, Yr26 in ten genotypes, Yr29 in 22 genotypes, Yr36 in 12 genotypes, Yr44 in 30 genotypes, and Yr62 in 51 genotypes. No line had Yr5 , Yr8 , Yr10 or Yr15 . Complete or all stage resistance was observed in genotypes carrying gene combinations Yr9 + Yr18 + Yr44 + Yr62, Yr29 + Yr62 + Yr26 and Yr9 + Yr17 + Yr26 + Yr44 + Yr62. The results are helpful for developing wheat cultivars with effective and more durable resistance to stripe rust both in China and Ethiopia.

Physical information of 2705 PCR-based molecular markers and the evaluation of their potential use in wheat - Chunhua Zhao; Han Sun; Chunhui Guan; Junpeng Cui; Qianqian Zhang; Mengmeng Liu; Mengna Zhang; Qifan Guo; Yuzhu Hou; Mingjie Xiang; Xiaomin Jiang; Xiulong Luo; et al. (Journal of Genetics, 2019)

Correction to: Genome-wide mapping of adult plant stripe rust resistance in wheat cultivar Toni - Xinli Zhou; Tian Hu; Xin Li; Ma YU; Yuanyuan Li; Suizhuang Yang; Kebing Huang; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2019)

Genome-wide mapping of adult plant stripe rust resistance in wheat cultivar Toni - Xinli Zhou; Tian Hu; Xin Li; Ma YU; Yuanyuan Li; Suizhuang Yang; Kebing Huang; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2019)

A major QTL co-localized on chromosome 6BL and its epistatic interaction for enhanced wheat stripe rust resistance - Qingdong Zeng; Jianhui Wu; Shengjie Liu; Shuo Huang; Qilin Wang; Jingmei Mu; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2019)

Stripe rust resistance to a burgeoning Puccinia striiformis f. sp. tritici race CYR34 in current Chinese wheat cultivars for breeding and research - Licheng Wang; Xinrui Tang; Jianhui Wu; Chuan Shen; Miaofei Dai; Qilin Wang; Qingdong Zeng; Zhensheng Kang; Yunfeng Wu; Dejun Han (Euphytica, 2019)

Genetic architecture of wheat stripe rust resistance revealed by combining QTL mapping using SNP-based genetic maps and bulked segregant analysis - Jingmei Mu; Shuo Huang; Shengjie Liu; Qingdong Zeng; Miaofei Dai; Qilin Wang; Jianhui Wu; Shizhou Yu; Zhensheng Kang; Dejun Han (Theoretical and Applied Genetics, 2019)

Comparative genome-wide mapping versus extreme pool-genotyping and development of diagnostic SNP markers linked to QTL for adult plant resistance to stripe rust in common wheat - Jianhui Wu; Shuo Huang; Qingdong Zeng; Shengjie Liu; Qilin Wang; Jingmei Mu; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

SNP-based pool genotyping and haplotype analysis accelerate fine-mapping of the wheat genomic region containing stripe rust resistance gene Yr26 - Jianhui Wu; Qingdong Zeng; Qilin Wang; Shengjie Liu; Shizhou Yu; Jingmei Mu; Shuo Huang; Hanan Sela; Assaf Distelfeld; Lili Huang; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

Rapid identification of an adult plant stripe rust resistance gene in hexaploid wheat by high-throughput SNP array genotyping of pooled extremes - Jianhui Wu; Shengjie Liu; Qilin Wang; Qingdong Zeng; Jingmei Mu; Shuo Huang; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

Evaluation of resistance of current wheat cultivars and breeding lines to stripe rust from three Gorges reservoir area - Yuheng Yang; Fajing Chen; Dejun Han; Renwu Ruan; Boqun Li; Yang Yu; Chaowei Bi (Journal of General Plant Pathology, 2017)

Rapid identification of a major effect QTL conferring adult plant resistance to stripe rust in wheat cultivar Yaco“S” - Haiyang Li; Qilin Wang; Liangsheng Xu; Jingmei Mu; Jianhui Wu; Qingdong Zeng; Shizhou Yu; Lili Huang; Dejun Han; Zhensheng Kang (Euphytica, 2017)

Inhibitory action of chamaejasmin A against human HEP-2 epithelial cells: effect on tubulin protein - Yan Zhao; Fenglian Wu; Yu Wang; Shengwu Chen; Guojun Han; Ming Liu; Dejun Jin (Molecular Biology Reports, 2012)

SSR and STS markers for wheat stripe rust resistance gene Yr26 - Chunmei Wang; Yiping Zhang; Dejun Han; Zhensheng Kang; Guiping Li; Aizhong Cao; Peidu Chen (Euphytica, 2008)

Expression Profiles of 10,422 Genes at Early Stage of Low Nitrogen Stress in Rice Assayed using a cDNA Microarray - Xingming Lian; Shiping Wang; Jianwei Zhang; Qi Feng; Lida Zhang; Danlin Fan; Xianghua Li; Dejun Yuan; Bin Han; Qifa Zhang (Plant Molecular Biology, 2006)